CAPITAL MARKET LITERACY AND STUDENTS INVESTMENT DECISIONS - Gusni Tanjung; Siti Komariah; Syamsu Yusuf (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
Capital market literacy is presents to give knowledge and experience to students as young investors with no experience in capital market investment products and transactions. The purpose of this research is to find out the role of capital market literacy to encourage students in making the right investment decisions. The unit analysis of this research was an active student of Widyatama University who has followed capital market school and become investors in the Indonesia capital market. This is preliminary research that only using simple statistical descriptive techniques about the number of students investors and their transaction values. The results showed that capital market literacy through capital market schools has an important role in increasing student investment interest and investment decisions which are reflected in the increasing trend of student investors and the value of their transactions in the capital market.